Hazardous Effects of Electrocautery on Penile Arteries: An Experimental Study - Binali Fırıncı; Remzi Arslan; Özgür Çağlar; Ali Ahıskalıoğlu; Mehmet Dumlu Aydın (Journal of Behçet Uz Children's Hospital, 2023)
Objective: Urethral arteries may be affected during electrocauterization The present study aims to investigate whether urethral artery spasm induced by electrocauterization during penile surgery causes pudendal nerve injury. Method: Eighteen male New Zealand rabbits were allocated into control (G-I, n=5), penile surgery without electrocauterization (SHAM group, G-II, n=6) and monopolar cauterization under general anesthesia (study group, G-III, n=9) groups. The animals were followed up for three weeks and then sacrificed. Vasospasm index values (VSI: wall ring surface value/lumen surface value) of urethral arteries and degenerated neuron densities (DNDs) of pudendal nerve dorsal root ganglia at sacral-3 level (S3) were examined using stereological methods. Results were compared using the one-way ANOVA test. Results: Neuronal angulation, cytoplasmic condensation, nuclear shrinkage, and condensed nuclei were detected in the pudendal nerve ganglia. The mean VSI values of urethral arteries and DNDs of pudendal ganglia (n/mm3) were estimated as 1.012+-0.024 vs. 4+-1 in GI; 1.082+-0.323 vs. 28+-7 in GII and 2.54+-0.0621 vs. 137+-14 in GIII, respectively. Statistical significance values (p-values) in terms of VSI, and DND for the differences between GI and GII (p<0.01 vs. p<0.005), GII and GIII (p<0.001 vs. p<0.0001)- and GI and GIII (p<0.0001 vs. p<0.0001) were as indicated. Conclusion: Electrocautery during penile surgery should not be used because of retrograde degeneration of the pudendal nerve and ganglia secondary to the injury to urethral taste bud-like structures.